The Effect of Comprehensive Caring Training on Caring Behavior of Nurses - Gusni Fitri; Rizanda Machmud; Vetty Priscilla (LPPM STIKES KENDAL, 2020)
Raden Mattaher General Hospital, Jambi Province is a referral hospital and there are still unfriendly nurses and talkers, taking action in a hurry. This indicates that there is still a lack of caring behavior in patients. This study aims to identify the effect of comprehensive caring training on caring behavior of nurses at Raden Mattaher Regional General Hospital Jambi Province. This research was conducted in the Class 3 Inpatient Room. The time of the study was 15 January - 11 April. The statistical test that was carried out to see the average difference between observations was also carried out a statistical test of the mean difference between groups with the GLM analysis repeated measures with the simple firs model. The population in this study were 165 nurses in the third class inpatient room. The sample consisted of 22 respondents. The results of the study showed that there was a significant effect (< 0.05) of comprehensive caring training on the knowledge, attitudes and skills of nurse caring behavior at the Raden Mattaher Regional General Hospital, Jambi Province. It is hoped that there will be material on the form of caring behavior that can be easily read by nurses and carried out periodic supervision.